DETERMINASI PERILAKU MENABUNG GENERASI Z: DENGAN LITERASI KEUANGAN SEBAGAI PEMEDIASI - Riri Ariyanti; Wida Purwidianti; Suryo Budi Santoso; Bima Cinintya Pratama (Jurnal Proaksi, 2024)
Financial literacy is information on financial management as a basic need for individuals to improve community welfare and avoid financial problems by getting used to saving behavior. This study aims to examine the influence od social factors (parents and peers), self-control, and financial education on saving behavior among Generation Z, with financial literacy serving as a mediating variable. The population of this study comprises Generation Z individuals aged 15-29 years in there regencies in Central Java, namely Banjarnegara, Purbalingga, and Banyumas (barlingmas), totaling 888,447 people. Data analysis conducted using SEM PLS. From the research results, it shows that social factors, self-control, financial education do not have a significant influence on saving behavior. While social factors, self-control are not mediated by financial literacy but financial education is mediated by financial literacy. This study shows the importance of financial literacy and financial education for Generation Z in Barlingmas Regency which will have a positive influence on saving behavior.